Impact of small vessel disease on severity of motor and cognitive impairment in Parkinson's disease. (December 2018) - Schwartz, Raymond S.; Halliday, Glenda M.; Soh, Derrick; Cordato, Dennis J.; Kril, Jillian J.
Highlights: Significant correlation: small vessel disease and motor impairment (autopsy proven). Significant correlation: hypertension and dementia severity. Important to manage vascular risk factors in PD patients. Abstract: Background: Subcortical small vessel disease and vascular risk factors are associated with motor and cognitive impairment. In this study we examined the relationship between these factors and the severity of motor impairment and dementia in pathologically-confirmed Parkinson's disease (PD). Methods: The extent and severity of small vessel disease (SVD) was assessed pathologically in 77 patients with PD. The severity of motor impairment was determined using a cumulative index derived from longitudinal measures of Hoehn and Yahr score. The presence of dementia was scored using the Clinical Dementia Rating. The presence or absence of vascular risk factors and stroke were also recorded. Interactions were assessed using stepwise multiple regression analyses. Results: Significant correlations were demonstrated between perivascular pallor in the globus pallidus interna and the Hoehn and Yahr stage and between increasing Braak PD stage, the number of vascular risk factors and dementia. Among the vascular risk factors, hypertension was the only variable to independently correlate with dementia. SVD pathology did not correlate with dementia in our cohort. Conclusions: This study demonstrates an association between SVD and motor impairment, and between vascular risk factors, particularly hypertension, and dementia in PD and highlights the need to manage vascular co-morbidities in PD patients.